Quality of life of elderly patients in life–threatening conditions - Wysokiński, Mariusz; Fidecki, Wiesław; Adamiec, Robert; Burian, Jadwiga (Nursing in the 21st Century, 2011)
Aim. The work aimed at attempting to assess the quality of life of elderly patients in life-threatening conditions.Material and methods. The work made use of the diagnostic poll method based on a questionnaire. WHOQOL – BREF (World Health Organization Quality of Life Questionnaire) was the standardised research tool which was employed for this investigation. The research involved 102 people, aged over 65.Results. Elderly people evaluated both their general quality of life and their health perception on an average level. A significant negative correlation was found between the quality of life and age. Males were found to have a slightly better general quality of life evaluation and health perception than females. Among elderly patients, it was the people with higher education that had significantly better general quality of life. Elderly people who were in a relationship had better quality of life in all domains as well as general quality of life, and general perception of health than single people.Conclusions. Elderly patients evaluated their quality of life and their health state as average. Quality of life depended on age and education of investigated elderly patients involved in this research.